A Study on the Dose and Image Quality for Reduction of the Patient’s Lens Dose Using Nano Tungsten Shield in Brain Perfusion CT - Kim, Dae Ho; Kim, Sang Hyun (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: Brain Perfusion CT is an important examination for diagnosing cerebral infarction. However, doses of the lens of the patient in Brain Perfusion CT are very high. Therefore, purpose of this study is to reduce the dose received by the lens of a patient without affecting the image quality. Methods/Statistical analysis: To evaluate the exposure dose of the lens of the patient during Brain Perfusion CT, brain perfusion CT was taken at 100 ± 20 kVp and 360 ± 20 mAs. PLD was inserted at each lens position of the Rando phantom composed of human equivalents, and the dose was repeated five times at the same position, depending on the presence or absence of a tungsten shield composed of nano-sized particles. Image quality evaluation in this study is based on the RMSE, CC, MSSIM, PSNR was used. Findings: In comparison with the case of using a self-made shield and no use, the lens showed a difference of minimum 39.7 and maximum 85.9 mGy in Brain Perfusion CT. As a result of evaluating the difference of images according to the application of nano-sized tungsten shield, the mean square root error (RMSE) was 35.1 ± 0.3, the correlation coefficient (CC) was 0.93 ± 0.03 in Brain perfusion CT, and the average structural similarity (MSSIM) was 0.91 ± 0.01, the maximum signal-to-noise ratio (PSNR) was 27.0 ± 1. Improvements/Applications: In conclusion, use of self-produced nanotungsten shielding is believed to solve the problem of exposure of high doses to the patient’s lens during a brain perfusion CT examination, which does not affect the image.